2020
DOI: 10.1002/ajb2.1474
|View full text |Cite
|
Sign up to set email alerts
|

A combination of morphological and photosynthetic functional traits maintains the vertical distribution of bryophytes in a subtropical cloud forest

Abstract: Premise The distribution and performance of bryophyte species vary with vertical gradients, as a result of changes in environmental factors, especially light. However, the morphological and physiological drivers of bryophyte distribution along forest vertical gradients are poorly understood. Methods For 18 species of mosses and liverworts distributed among three vertical microhabitats (ground, tree trunk, and branch, variance in 28 morphological and photosynthetic functional traits was comparatively analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…The photosynthetic rates reported in the present study are within the ranges previously reported for mosses (Alpert & Oechel, 1987;Williams & Flanagan, 2002;Brodribb et al, 2007Brodribb et al, , 2020Waite & Sack, 2010;Hanson et al, 2014;Wang et al, 2014;Carriquí et al, 2019;Fan et al, 2020;Perera-Castro et al, 2020a,b, c). The two Polytrichum species achieved the largest A N and g m due to their specific characteristics, as already shown by Carriquí et al (2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The photosynthetic rates reported in the present study are within the ranges previously reported for mosses (Alpert & Oechel, 1987;Williams & Flanagan, 2002;Brodribb et al, 2007Brodribb et al, , 2020Waite & Sack, 2010;Hanson et al, 2014;Wang et al, 2014;Carriquí et al, 2019;Fan et al, 2020;Perera-Castro et al, 2020a,b, c). The two Polytrichum species achieved the largest A N and g m due to their specific characteristics, as already shown by Carriquí et al (2019).…”
Section: Discussionsupporting
confidence: 92%
“…Bryophyte photosynthesis-that is, photosynthetic efficiency and limitationshas been scarcely studied in comparison to that of spermatophytes (Flexas et al, 2018;. However, there is evidence on how low their net CO 2 assimilation (A N ) rates are as compared to other land plants groups (Alpert & Oechel, 1987;Williams & Flanagan, 2002;Brodribb et al, 2007Brodribb et al, , 2020Waite & Sack, 2010;Hanson et al, 2014;Wang et al, 2014;Carriquí et al, 2019;Gago et al, 2019;Fan et al, 2020;Perera-Castro et al, 2020a,b,c). Recently, Carriquí et al (2019) performed a detailed study analysing which traits limited photosynthesis in the gametophytes of several bryophyte species.…”
Section: Introductionmentioning
confidence: 99%
“…While in some cases these groupings may resemble the more traditional "life-form" or "growth-form" types of classification, they regularly do not (e.g. Fan et al 2020). While trait correlations have been identified with photosynthetic traits (Waite & Sack 2011, Wang et al 2014, 2017a&b, Mazziotta et al 2019, the relationship between photosynthetic traits and water relations is more complicated, and potentially phylogenetically constrained (Wang & bader 2018).…”
Section: Multiple and Taxon Specific Scales Of Interactionmentioning
confidence: 99%
“…Sierra et al 2019, Marks et al 2019a, sub-tropical (e.g. Wang et al 2017b, Fan et al 2020) and mediterranean (e.g. Fernández-Martínez et al 2019, Spitale et al 2020 biomes, much of the work continues to focus on higher-latitude ecosystems, especially in the northern hemisphere.…”
Section: What Are the Gaps In Our Functional Trait Studies?mentioning
confidence: 99%
“…Chlorophyll content, active Fe content, and chlorophyll uorescence parameters are major physiological indicators for studying plant physiological processes [41]. In this study, the SPAD value was used to evaluate the effects of NCFe on the chlorophyll content in leaves (Fig.…”
Section: Enrichment Of Physiological Indicators Facilitated By Ncfementioning
confidence: 99%